A failure criterion for RC beams subjected to axial and transverse loadings. (1st November 2021) - Wahbi, Amal; Pham, Duc Toan; Hassen, Ghazi; Garnier, Denis; de Buhan, Patrick
Highlights: Failure criterion for RC beams subjected to axial and transverse loads is proposed. Semi-analytical solution is confirmed by numerical simulations and other methods. Parametric studies show the influence of reinforcement ratios on strength domain. Theoretical prediction appears to be in a good agreement with experimental results. Abstract: The upper bound kinematic approach of yield design is developed for the design of reinforced concrete (RC) beams subjected to the combination of transverse and axial loadings. The method is implemented by considering a simple virtual collapse mechanism in which the beam is divided into two rigid blocks separated by a plane. Each block is given a virtual motion of translation as well as of rotation about its support. An optimization of the problem is then formulated, resulting in an upper bound to the strength condition of the RC beam in terms of axial and transverse loading parameters. These theoretical predictions are then compared to the results derived from numerical simulations of the same problem using a finite element-based limit analysis software (which can consider much more complex failure mechanisms than the one considered). Finally, in order to assess their practical validity, predictions from the proposed method are also compared to other predictive methods, as well as to some available experimental results published in the literature.